EFEKTIVITAS HIDROTERAPI DAN RELAKSASI BENSON TERHADAP ASUHAN KEPERAWATAN PADA PENDERITA HIPERTENSI PASIEN RSUD TUGUREJO SEMARANG - Akbriani, Azizza Jasmine; Supriyanto, Agung; Terta, Riko Ardi; Jamaluddin, M. (NHM PRESS, 2023)
Background :The prevalence of dangerous and life-threatening non-communicable diseases, especially hypertension, makes health workers, namely nurses, interested in nursing innovation in providing nursing care to reduce blood pressure, both systolic and diastolic, with a combination technique of giving hydrotherapy and benson relaxation. determine the effectiveness of hydrotherapy and benson relaxation on nursing care in hypertensive patients in Tugurejo Hospital, Semarang. Research Methods: this study uses a case study method with a purposive sampling technique. The number of samples consisted of 4 patients who were given the same treatment. The instruments used were Hydrotherapy SOP, Benson Relaxation SOP, blood pressure observation sheet, informed consent. Research result: Based on the results of the analysis using manual calculations, it was found that the administration of hydrotherapy and benson relaxation in patients with hypertension experienced a decrease in both systolic and diastolic pressure. Conclusion: there is the effectiveness of hydrotherapy and benson relaxation on nursing care in hypertensive patients at Tugurejo Hospital, Semarang.